Nature-Based One Health Approaches to Urban Agriculture Can Deliver Food and Nutrition Security - Ebenso, Bassey; Otu, Akaninyene; Giusti, Alessandro; Cousin, Philipe; Adetimirin, Victor; Razafindralambo, Hary; Effa, Emmanuel; Gkisakis, Vasileios; Thiare, Ousmane; Levavasseur, Vincent; Kouhounde, Sonagnon; Adeoti, Kifouli; et al. (Frontiers in Nutrition, 2022)
The increasing global human population is projected to reach 9.7 billion people by 2050. This population growth is currently linked to the trends of world-wide urbanization, growth of megacities and shifting dietary patterns. While humankind faces the daunting challenge of feeding and providing healthy lives for its teeming populations, urban agriculture holds promise for improving the quality of life in cities. Fortunately, policymakers and planners are accepting the need to support urban fringe farmers to increase the resilience of food systems while efficiently managing already strained natural resources. We argue that for urban agriculture to significantly increase food yields, it is crucial to adopt a One Health approach to agriculture and environmental stewardship. Here, we propose six nature-based and climate-smart approaches to accelerate the transition towards more sustainable food systems. These approaches include reducing the reliance on synthetic agricultural inputs, increasing biodiversity through producing locally adapted crops and livestock breeds, using probiotics and postbiotics, and adopting portable digital decision-support systems. Such radical approaches to transforming food production will require cross-sectoral stakeholder engagement at international, national, and community levels to protect biodiversity and the environment whilst ensuring sustainable and nutritious diets that are culturally acceptable, accessible, and affordable for all.